Strategi Peningkatan Kinerja Karyawan Taman Buah Mekarsari - Rika Kusumawati; M. Syamsul Maarif; Sri Nurdiati (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Human resources are the main element of the organization. The organization goals will be achieved when ITS employees have high performance. The purposeS of this study were to analyze the effect of competency on employee motivation, the effect of competency on employee performance, and the effect of motivation on employee performance, and to formulate strategies for improving the employee performance at Mekarsari Fruit Garden. The respondents in this study were 167 employees selected with sampling technique using stratified random sampling. Analysis of the data used in this research included descriptive analysis of respondents, Spearman correlation test methods, analysis Structural Equation Modeling (SEM) with LISREL 8.51 and Analytical Hierarchy Process (AHP) with expert choice 2000. The results showed that 1) Competency had an effect on employee motivation at Mekarsari Fruit Garden; 2) Competency had an effect on employee performance at Mekarsari Fruit Garden; 3) Motivation had an effect on employee performance at Mekarsari Fruit Garden. The first strategy to improve employee performance was improving the prosperity of employees, and the highest factor in increasing employee performance was competency. The most influential actor was the President Director of Mekarsari Fruit Garden whereas the highest score of the objective was increasing the profit of Mekarsari Fruit Garden.Keywords: performance, competency, motivation, strategies, Mekarsari Fruit GardenAbstrak: Sumber Daya Manusia (SDM) merupakan elemen utama organisasi. Tujuan organisasi akan tercapai bila pegawai di dalamnya memiliki kinerja yang tinggi. Tujuan penelitian ini adalah untuk mengalisis pengaruh kompetensi terhadap motivasi karyawan, kompetensi terhadap kinerja karyawan dan motivasi terhadap kinerja karyawan serta merumuskan strategi dalam rangka peningkatan kinerja karyawan Taman Buah Mekarsari. Responden dalam penelitian ini sebanyak 167 karyawan dengan teknik penarikan contoh menggunakan Stratified Random Sampling. Analisis data yang digunakan dalam penelitian ini meliputi analisis deskriptif responden, uji korelasi dengan metode Spearman, analisis Structural Equation Modeling (SEM) dengan LISREL 8.5, dan analytical hierarchy process (AHP) menggunakan expert choice 2000. Hasil penelitian menunjukkan bahwa: 1) Kompetensi berpengaruh terhadap motivasi karyawan Taman Buah Mekarsari; 2) Kompetensi berpengaruh terhadap kinerja karyawan Taman Buah Mekarsari; 3) Motivasi berpengaruh terhadap kinerja karyawan Taman Buah Mekarsari. Strategi pertama untuk meningkatkan kinerja karyawan adalah meningkatkan kesejahteraan karyawaan, sementara faktor tertinggi dalam hal peningkatan kinerja adalah kompetensi. Aktor yang paling berpengaruh dalam peningkatan kinerja karyawan adalah Direktur Utama, sementara skor tertinggi dari tujuan adalah meningkatkan laba Taman Buah Mekarsari.Kata kunci: kinerja, kompetensi, motivasi, strategi, taman buah mekarsari